Related Case Of Current Process Of Claiming Oleh Children Through Restorative Justice In The Way Of Law Polres Binjai - Ferry Irmawan; Firman Halawa; Muhammad Arif Sahlepi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Traffic accidents involving juvenile perpetrators often raise controversy in the implementation of criminal law, causing much polemic. The view that the legal process should be carried out and enforced without the rule of law and law enforcement is that the "passage" that includes the delict of guilt, that is, at the time of driving the vehicle to cause the occurrence of an accident and resulting death of the victim, should still be processed legally. The large number of traffic accidents involving minors is a serious concern for parents and governments. The State of Indonesia guarantees a basic principle of the application of the law to the child, which we can see in Article 16, Paragraph 3, of the Act No. 35 of 2014 on the Protection of the Child, which states that “arrest, detention, or criminal imprisonment is only carried out when it is in accordance with the applicable law and can only be done as a last resort. The concept of restorative justice in the settlement of traffic accident cases is intended to realize a shift of the criminal settlement process out of the criminal court process and resolved through the process of divorce. The police action in settling the traffic accident case by a minor child is to begin with the operation of the Place of Evidence of Things (TCP), to make news of the event, to carry out the investigation process, and to give time to the victims and perpetrators to punch. From this process begins the restorative justice, so that if the victim and the perpetrator are willing to peace and the offender is willing to pay damages, the parties make a peace declaration